2020
DOI: 10.3390/diagnostics10030142
|View full text |Cite
|
Sign up to set email alerts
|

Post-Treatment Thyroid Diseases in Children with Brain Tumors: A Single-Center Experience at “Prof. Dr. Ion Chiricuță” Institute of Oncology, Cluj-Napoca

Abstract: Aim of study: The purpose of the study was to evaluate the association of thyroid dysfunction occurring in pediatric patients treated for brain tumors. Patients and methods: A total of 255 patients with brain tumors were treated between 2001 and 2018 at the “Prof. Dr. Ion Chiricuță” Institute of Oncology, Cluj-Napoca. Due to a minimum follow-up of 4 years, we studied 184 out of the 255 patients. The cohort included 69 girls (37.5%) and 109 boys (62.5%), with a median age of 8.4 years. The evaluated tumors incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…In pediatric patients, an important probability of developing thyroid dysfunction was found post-treatment with surgery, chemotherapy, and radiotherapy ( Jin et al, 2018 ; Cosnarovici et al, 2020 ); moreover, abnormalities in thyroid function were found in patients with AQP4 antibody–seropositive optic neuritis ( Zhao et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pediatric patients, an important probability of developing thyroid dysfunction was found post-treatment with surgery, chemotherapy, and radiotherapy ( Jin et al, 2018 ; Cosnarovici et al, 2020 ); moreover, abnormalities in thyroid function were found in patients with AQP4 antibody–seropositive optic neuritis ( Zhao et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In pediatric patients, an important probability of developing thyroid dysfunction was found post-treatment with surgery, chemotherapy, and radiotherapy (Jin et al, 2018;Cosnarovici et al, 2020); moreover, abnormalities in thyroid function were found in patients with AQP4 antibody-seropositive optic neuritis (Zhao et al, 2017). We previously identified a negative modulator of AQP4 protein and demonstrated that triiodothyronine (T3) treatment of GBM-95-line cells resulted in a slight reduction in cell migration (Costa et al, 2019); other studies have also evaluated the modulatory action of this hormone on the expression of AQP4 in stroke animal models (Sadana et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Hypothyroidism is a prevalent endocrine disorder in patients with MB, primarily considered a consequence of aggressive tumor treatments, particularly craniospinal irradiation 15,16 . However, the potential impact of hypothyroidism on MB progression has remained unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…In the brain, thyroid receptor α1 (TRα1) predominates and serves as a transcription factor for regulating the transcription of TH target genes, including Krueppel-like factor 9 ( Klf9 ) and hairless ( Hr ) 14 . Patients with MB commonly exhibit hypothyroidism (reduced plasma levels of TH), which is classically considered a treatment-related complication 15,16 . A possible role of TH, or hypothyroidism, in MB pathogenicity has never been investigated.…”
Section: Introductionmentioning
confidence: 99%